2021
DOI: 10.3389/fnut.2021.650211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Citrus Pulp or Inulin on Intestinal Microbiota and Metabolites, Barrier, and Immune Function of Weaned Piglets

Abstract: We investigated the use of citrus pulp (CP) as a novel prebiotic capable of exerting microbiota and immunomodulating capacities to alleviate weaning stress. Inulin (IN), a well-known prebiotic, was used for comparison. Hundred and 28 male weaned piglets of 21 days old were assigned to 32 pens of 4 piglets each. Piglets were assigned to one of the four treatments, i.e., control, IN supplemented at 0.2% (IN0.2%), and CP supplemented either at 0.2% (CP0.2%) or at 2% (CP2%). On d10–11 and d31–32 post-weaning, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…What is more, the relieved diarrhea incidence resulting from ZnO and C_ZnO treatment was also in line with the notable effect of ZnO (19,20). Diarrhea was accompanied by ruined villi and a slow cell renewal rate, leading to disorders of nutrient absorption, eventually causing growth retardation in weaned piglets (21). In the present research, ZnO and C_ZnO both elevated the villus height in the foregut, which broadened the intestinal absorption surface area.…”
Section: Discussionsupporting
confidence: 84%
“…What is more, the relieved diarrhea incidence resulting from ZnO and C_ZnO treatment was also in line with the notable effect of ZnO (19,20). Diarrhea was accompanied by ruined villi and a slow cell renewal rate, leading to disorders of nutrient absorption, eventually causing growth retardation in weaned piglets (21). In the present research, ZnO and C_ZnO both elevated the villus height in the foregut, which broadened the intestinal absorption surface area.…”
Section: Discussionsupporting
confidence: 84%
“…Each pen, housing 6 piglets of 3 barrows and 3 gilts, represented an experimental unit. The dietary inclusion at the level of 0.75% for the three prebiotics and the oat b-glucan in the experimental diets were to reflect the ranges of their dietary supplementation levels reported in the current literature (Mair et al, 2010;Park et al, 2018;Xing et al, 2018;Uerlings et al, 2021) in hopefully eliciting positive changes in growth performance, nutrition and and/or physiological endpoints while also being economically feasible for the industry should commercial applications of these potential gut modifiers as feed additives be attempted.…”
Section: Experimental Diets and Designmentioning
confidence: 99%
“…Furthermore, Mair et al (2010) added inulin to weaning pig diets at 0.40% and could not find any improvements in growth performances. Uerlings et al (2021) shown citric pulp supplemented at 0.20% was equivalent to 0.20% inulin in improving intestinal parameters in weanling pigs. Again, results of this study and the reviewed literature reports of different dietary supplementation levels of inulin as a potential gut modifier feed additive conducted under various experimental conditions do not support improvements in promoting growth performances in weanling pigs.…”
mentioning
confidence: 91%
See 2 more Smart Citations